Working in Groups on Practical Engineering Activities with Young Children - Cerovac, Milorad; Seemann, Kurt; Keane, Therese (Design and Technology Education: An International Journal, 2020)
Australia has a long-standing interest in fostering innovation capabilities to drive its future prosperity. However, it has only been in recent years that an emphasis on developing these capabilities has been formally extended into the classroom through the introduction of the Australian Curriculum Technologies. In 2017, the State Government of Victoria implemented its version of this national curriculum for the Technologies domain. For educators, this recent implementation could be considered problematic, for unlike the traditions of literacy and numeracy, methods to assist classroom teachers in diagnosing developmental indicators, for applied spatial problem-solving among children appears to be lacking in the Technologies area. Without such methods of diagnosis, it can be argued that teachers may struggle to develop appropriately targeted lessons, that demand of the student, the ability to comprehend applied spatial problem-solving, such as with hands-on engineering activities. Our research aims to investigate how a child’s applied spatial inferential reasoning capabilities, vary by developmental age. To answer this question, we have adopted a two-stage process. Stage One involves a pilot study testing and refining the key research instruments. Stage Two incorporates the main study involving a larger number of participants. This paper summarises early insights from a mixed-method pilot study involving 15 students (9 boys, 6 girls) from Years 3-12. Students enrolled in this study undertook one of three hands-on problem-based engineering activities categorised as simple, complicated or complex; working in small groups of three. We noted that gender makeup of the group, and age levels of participating students appeared to be variables that impacted on organisation, communication and the solution produced. These preliminary observations assisted to refine the key indicators for observing students in preparation for the main study. Key interests in this study include the student’s capacity for inference-making and abstraction with respect to spatial problem-solving. A review of the relevant literature and the need for further research in spatial reasoning is discussed.